2022
DOI: 10.1371/journal.pone.0270982
|View full text |Cite
|
Sign up to set email alerts
|

Different phylotypes of Cutibacterium acnes cause different modic changes in intervertebral disc degeneration

Abstract: Background The contribution of Cutibacterium acnes (C. acnes) infection to intervertebral disc degeneration (IDD) and the antibiotic therapy has evoked several controversies in recent years. While some microbiology studies report bacterial disc infection within IDD patients, others attribute the positive results to contamination during prolonged cultures. In addition to the clinical controversy, little was known about the mechanism of C. acnes-caused Modic changes (MCs) if C. acnes was the pathogenic factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…acnes has different and distinct evolutionary lineages, with the designated phylotypes IA1, IA2, IB, IC, II, and III being based on Multilocus Sequence Typing and Whole Genome Sequencing [38]. Each phylotype has a specific pathogenicity mechanism and produces virulence factors that, depending on the tissue they are colonizing, can trigger an inflammatory response or remain inert to the host's immune system [34,39]. Rollason et al highlighted the high proportion of phylotype II among positive IVD cultures from patients with LDD [40]; this phylotype produces the enzyme hyaluronate lyase (HYL), which degrades hyaluronic acid, an important component of ECM in IVDs, by contributing to its degeneration [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…acnes has different and distinct evolutionary lineages, with the designated phylotypes IA1, IA2, IB, IC, II, and III being based on Multilocus Sequence Typing and Whole Genome Sequencing [38]. Each phylotype has a specific pathogenicity mechanism and produces virulence factors that, depending on the tissue they are colonizing, can trigger an inflammatory response or remain inert to the host's immune system [34,39]. Rollason et al highlighted the high proportion of phylotype II among positive IVD cultures from patients with LDD [40]; this phylotype produces the enzyme hyaluronate lyase (HYL), which degrades hyaluronic acid, an important component of ECM in IVDs, by contributing to its degeneration [41].…”
Section: Discussionmentioning
confidence: 99%
“…HYL has two variants, with the HYL-IB/II variant, which is found in phylotypes IB and II, being the most active [41,43]; phylotypes IB and II also secrete the cytotoxin CAMP-1 (Christie-Atkins-Munch-Petersen factor), which has a strong interaction with Toll-like receptor 2, amplifying the inflammatory response in the IVD microenvironment [33,44]. In an animal model study, Lan et al demonstrated a positive effect of phylotypes IB and II on the expression of MMP-13 (Matrix Metallopeptidase 13), which is active in the degradation of collagen, an important component of the annulus fibrosus in IVDs [34]. Our preliminary results demonstrate a high frequency of phylotypes IB and II, which were isolated in association in 42.9% of the positive samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Columbia agar w/5% sheep blood is a highly nutritious medium for cultivating and isolating difficult-to-grow microorganisms and is less porous than the MH agar, leading to a lower diffusion rate [71]. Studies on anti-acne efficacy suggested the possible cultivation of CBA and MH agar under aerobic conditions; however, no growth was observed after a cultivation period of 2 weeks with consistent checking [40,72]. G-ZnO NPs exhibit a distinctive zone of inhibition against S. aureus of 19 ± 1 mm.…”
Section: Anti-acne Efficacymentioning
confidence: 99%
“…Такі зміни, за популяційної поширеності для поперекового відділу хребта на рівні ~6 % [52], гіпотетично так чи інакше пов'язані з патологією міжхребцевих дисків (див. [3,30,65]), можливо і через запальну ланку, обумовлену колонізацією ушкодженого міжхребцевого диску коменсальною бактерією Cutibacterium acnes [3,4,18,30,33,44,53,62,63] (дискусія: [9,16,47,65], [25] і [32], [10] і [31]). У якості можливого додаткового фактору ризику болю у спині розглядають поширені серед дорослих дефекти добре іннервованих замикальних пластинок хребців (англ.…”
Section: другий клас включає патоморфологічні/патофізіологічні терміниunclassified